(untitled) (Proceedings of International Conference on Special Education, 2025)
This study investigates efficient teaching strategies for improving deaf students’ motivation in a higher education setting. In conventional educational environments, deaf students frequently encounter additional difficulties, especially in communication and engagement, which may have an effect on their academic performance. This study used a quantitative descriptive design to survey deaf students in a higher education setting to assess the effectiveness of different teaching strategies, such as lectures based on sign language, collaborative work, and visual aids, and to examine how these approaches differ in their effects among deaf students. The results indicate that lectures that integrate sign language and cooperative group activities greatly improve motivation and attentiveness in both genders. However, while female students responded more favorably, male students showed a preference for visual-spatial instructional methods that helped reduce external distractions. Furthermore, having qualified sign language interpreters on hand proved to be essential for helping the students stay focused and increase motivation. By highlighting the significance of gender-sensitive teaching strategies for deaf students, this study adds to the body of literature on inclusive education. According to the information acquired, educational institutions require to use adaptable, differentiated teaching methods that accommodate the various learning requirements and preferences of deaf students. Such specialized methods improve educational equity and inclusivity in addition to creating a positive learning environment. To build on these findings and investigate other motivating elements that can help deaf adolescents succeed academically, more research is needed.